Course Outline dan Satuan Materi Sajian Berbasis Mutu di Perguruan Tinggi - Nurbayani, Etty (IAIN Samarinda, 2014)
A quality of lecturer is directed as a preparation of the profesional educational workers who have a broad knowledge, master on their field, able to manage and improve their profesionalisme, and able to administer the teaching skills. Ideally, a quality lecturer is able to implement three stages in teaching and learning process, they are : planning, implementation, and evaluation. The policy of Dean of STAIN Samarinda, to oblige the lecturers make a teaching plan in the form of course outline and lesson plan, is a real action to improve the quality of targetted teaching. A qualified lecturer should have a skill in planning a teaching process. A teaching plan can be developed based on the organization of teaching plan.